Whitehorse Rapids, Yukon Territory, ca. 1900 - Hester, Wilhelm, 1872-1947
Caption on image: (Lower left) General view of White Horse Rapids, N.W.T. (Lower right) Photo by W. Hester, Seattle, 11. Small boat in foreground. PH Coll 318.989 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number